The Impact of Street-Vended Bean Cake on Residents in Makurdi Town, Nigeria - Mchi, Akaawase Alexander; Akaawase, Doosuur Beatrice; Koffi, Ayadu Edwin (Journal of Multidisciplinary Research Advancements, 2024)
With the rate of urbanization in third-world cities, street-vended foods play a vital role in providing many urban residents with cheap, nutritious, and accessible food regardless of its safety, quality, and hygiene. This study assessed the impact of street-vended bean cake on residents in Makurdi town, Nigeria, which covered two council wards, namely North-Bank Ward I and North-Bank Ward II. A sample of 30 street-vended bean cakes was collected from vendors in 10 locations within Makurdi town for laboratory analysis. Miles and Misra's technique was performed in triplicate to determine the total bacterial counts. The vendor’s socioeconomic characteristics, cleanliness, and bean cake security were assessed. The bean cake vendors are between the age group 26 - 35 years. Most vendors have completed primary school and earn ₦11,000 - ₦25,000 monthly from bean cake vending.  Although 66.7 % of bean cake street vendors wear a neat apron and trim their nails short, however, 73.3 % serve their customers with bare hands, which implies a high possibility of bean cake contamination. It also implied that vendor’s hygiene factors and improper handling of bean cake can cumulatively affect the quality of bean cake available to Makurdi residents and could lead to loss of man-hour productivity. Four bacterial pathogens were identified in the study area; Bacillus spp. had the highest percentage (33.33 %), closely followed by Staphylococcus aureus (30.00%), Proteus spp. (20.00 %), while E. Coli maintained the least with (16.67%). The presence of Bacillus spp., Staphylococcus aureus, Proteus spp., and E. Coli implied a threat to human health. The study recommended proactive measures to be taken to forestall food-borne diseases, public awareness campaigns on food hygiene, and routine inspection of street bean cake vending locations.